Perceiving subject and social cognition. Remarks from Adolf Reinach, Shaun Gallagher and Dan Zahavi - Marco Tedeschini (Rosenberg & Sellier, 2016)
This paper deals with what Shaun Gallagher and Dan Zahavi call “the social cognition” from the chapter How we know others in their book The Phenomenological Mind (Gallagher, Zahavi 2008), and what Adolf Reinach calls the “extraneous perception” in his university course Einleitung in die Philosophie (Reinach 1913) – that is, the possibility of intersubjectivity, according to these authors. My objective is to show how Gallagher and Zahavi’s analyses could profit from that of Reinach. I find that Reinach’s study could provide a particular heuristic value to Gallagher and Zahavi’s work, by furnishing it with a useful tool to clear up some issues which, in my opinion, remain rather vague. The first part of this article is devoted to outlining Gallagher and Zahavi’s thesis about how we know others, clarifying which points of their analyses could be cleared up by Reinach’s study; the second part presents Reinach’s arguments concerning the perception of the other subject; and finally, I will explain how Reinach’s analysis contributes to that of Gallagher and Zahavi’s work and remark on what accessing to others’ mental state from the second-person perspective by combining the two positions means.